1978
DOI: 10.1007/bf01273258
|View full text |Cite
|
Sign up to set email alerts
|

Dysplastic gangliocytoma of the cerebellum—An ultrastructural study

Abstract: A case of dysplastic gangliocytoma of the cerebellum, a rare disorder with unknown etiology and pathogenesis, was studied ultrastructurally. The intranuclear inclusions identified were not seen to be of viral origin. The ultrastructural characteristics of the abnormal cells support the prevailing theory that these cells represent hypertrophied granular neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

1980
1980
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 6 publications
2
12
0
1
Order By: Relevance
“…Various additional abnormalities have been described in association with Lhermitte–Duclos disease (5, 15, 22). These include megalocephaly in about 50% of cases (3, 5, 10, 15, 17, 30, 34, 38), megalencephaly (5, 11, 15, 34, 37), syringomyelia (8, 19, 39), skeletal anomalies, such as polydactylia (8) and cranial asymmetry (10, 11, 14, 21, 34), multiple haemangioma (4, 5) and muco‐cutaneous lesions (3, 17, 29, 30). Table 2 gives an overview of additional malformations previously found to be associated with Lhermitte–Duclos tumour.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 3 more Smart Citations
“…Various additional abnormalities have been described in association with Lhermitte–Duclos disease (5, 15, 22). These include megalocephaly in about 50% of cases (3, 5, 10, 15, 17, 30, 34, 38), megalencephaly (5, 11, 15, 34, 37), syringomyelia (8, 19, 39), skeletal anomalies, such as polydactylia (8) and cranial asymmetry (10, 11, 14, 21, 34), multiple haemangioma (4, 5) and muco‐cutaneous lesions (3, 17, 29, 30). Table 2 gives an overview of additional malformations previously found to be associated with Lhermitte–Duclos tumour.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…From the very early case reports until the end of the 1970s, preoperative neuroimaging modalities to evaluate indirectly the mass effect of dysplastic cerebellar gangliocytoma mainly consisted of plain skull radiograms, vertebral angiography and ventriculography (2, 4, 5, 7–11, 13). Later, computed tomography (CT) became a sufficient radiographic tool to demonstrate the tumour mass, its distribution within the posterior fossa and its interference with the cerebellar parenchyma, nerval structures and CSF compartments more directly (3, 15, 34, 37, 41).…”
Section: Neuroradiological Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The recognition of the coexistence of Lhermitte-Duclos disease and multiple hamartoma-neoplasia syndrome, also called Cowden syndrome, by Padberg et al 17 suggested a genetic association between the two entities. 1 Today Lhermitte-Duclos disease or dysplastic gangliocytoma of the cerebellum is still a highly unusual and controversial condition.…”
Section: Introductionmentioning
confidence: 99%